La captivité en Allemagne des soldats juifs de France pendant la Seconde Guerre mondiale : l’ébauche d’un phénomène diasporique éphémère ? - Delphine Richard (Diasporas: Circulations, Migrations, Histoire)
About 13,000 Jewish soldiers were among the French POWs imprisoned in Germany from 1940 to 1945. If, as POW, they were put on the margins of the Shoah, their Jewishness singled them out in the captivity world, where they suffered anti-Semitism and discrimination. This issue of identity and common destiny brought these Jews together in each military camp, and triggered the emergence of ephemeral community forms with diasporic features.